2014
DOI: 10.1108/et-06-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Sports Development and Sports Management undergraduate students towards entrepreneurship

Abstract: Purpose – Given the high unemployment rates being experienced by graduates, the importance of small business start-up has increased significantly, with greater priority being placed upon the development of entrepreneurial skills across the educational sector. However, there is a limited literature considering the student experience and issues involved with supporting non-Business discipline students attaining entrepreneurial competencies. The purpose of this paper is to explore the attitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 34 publications
4
52
0
2
Order By: Relevance
“…This is supported by Hirschi and Fischer (2013) and Mohammad et al (2012) which stated that intention as an essential element in motivating an individual to become an entrepreneur (Table 5). Therefore, this situation can be explained and reinforced through the findings of studies by Nandram and Samson (2006), Ertuna andGurel (2011), Jones andJones (2014). They stated that a positive attitude towards an entrepreneurship career choice is formed through entrepreneurship education, formally or informally.…”
Section: Analysis Of the Relationship Between Attitudes And The Levelmentioning
confidence: 95%
See 3 more Smart Citations
“…This is supported by Hirschi and Fischer (2013) and Mohammad et al (2012) which stated that intention as an essential element in motivating an individual to become an entrepreneur (Table 5). Therefore, this situation can be explained and reinforced through the findings of studies by Nandram and Samson (2006), Ertuna andGurel (2011), Jones andJones (2014). They stated that a positive attitude towards an entrepreneurship career choice is formed through entrepreneurship education, formally or informally.…”
Section: Analysis Of the Relationship Between Attitudes And The Levelmentioning
confidence: 95%
“…Studies conducted by Jones and Jones (2014), suggested that an attitude of entrepreneurial motivation can increase the efficiency to exploit new market opportunities and improve value for money. In addition, originality of innovations can motivate an entrepreneur to be successful.…”
Section: Entrepreneurial Career Choicementioning
confidence: 99%
See 2 more Smart Citations
“…However, in spite of the increase of studies related to the intentions of university students, studies with students of nonbusiness disciplines have been scarce (Jones & Jones, 2014), and even more Sport Sciences'(SS) studies in our country (González-Serrano, Crespo, Pérez-Campos, & Calabuig, 2017). This is particularly worrying because, according to Ratten and Ferreira (2017), the trends in the sports industry reflect a growing need to be enterprising in products, services, technologies and market development.…”
Section: Introductionmentioning
confidence: 99%